The Structure of Women's Employment in Comparative Perspective - Becky Pettit; Jennifer Hook (Luxembourg Income Study (LIS), 2002)
One of the most dramatic social transformations of the latter half of the twentieth century involved the massive influx of women into the paid labor force. A central debate in studies of women's labor force participation concerns the influence of demographic and economic structures and institutional conditions on female employment. Single-country studies show consistent relationships between demographic and economic conditions and women's labor force participation. In contrast, comparativists emphasize institutional explanations for observed cross-national variation in aggregate levels of female employment. In this paper we analyze social survey data from 18 countries using multi-level modeling methods in an effort to synthesize structural and institutional accounts for variation in women's employment. Structural conditions including unemployment and service sector growth are important predictors of the overall level of women's employment. The effects of demographic characteristics on women's employment vary significantly across countries, and results suggest differences in policy context are associated with women's employment. In particular, federally supported child care is associated with an increase in the probability of employment among married women and women with children.
Keywords: 330; Weibliche Arbeitskräfte; Vergleich; Welt